Direct Surgery of Previously Coiled Large Internal Carotid Ophthalmic Aneurysm for the Purpose of Optic Nerve Decompression - Kawabata, Shuhei; Toyota, Shingo; Kumagai, Tetsuya; Goto, Tetsu; Mori, Kanji; Taki, Takuyu (Journal of Neurological Surgery Reports, 2017)
Background Progressive visual loss after coil embolization of a large internal carotid ophthalmic aneurysm has been widely reported. It is generally accepted that the primary strategy for this complication should be conservative, including steroid therapy; however, it is not well known as to what approach to take when the conservative therapy is not effective.Case Presentation We report a case of a 55-year-old female presenting with progressive visual loss after the coiling of a ruptured large internal carotid ophthalmic aneurysm. As the conservative therapy had not been effective, we performed neck clipping of the aneurysm with optic canal unroofing, anterior clinoidectomy, and partial removal of the embolized coils for the purpose of optic nerve decompression. After the surgery, the visual symptom was improved markedly.Conclusions It is suggested that direct surgery for the purpose of optic nerve decompression may be one of the options when conservative therapy is not effective for progressive visual disturbance after coil embolization.
Keywords: coiled aneurysm; clipping; mass effect; nerve decompression